Methodical instructions for independent work "Assessment of the situation in the event of an accident on water objects. Part 1" - Vambol, Sergij Oleksandrovich; Mezentseva, Iryna Oleksandrivna; Ilyinska, O. I.; Yevtushenko, N. S. (Національний технічний університет "Харківський політехнічний інститут", 2024)
These methodological instructions are intended for the independent work of students studying the discipline "Technological and ecological safety in the conditions of industrial and economic activity" in order to clarify the methodology for calculating the assessment of the situation in the event of an accident on water bodies. According to the study and work plans of the specialty 263, the educational program of the II (master's) level of higher education "Occupational safety", as part of the study of the mandatory professional discipline "Technogenetic-ecological safety in the conditions of industrial and economic activity", students are expected to independently perform the calculation task. Methodical instructions contain practical tasks that will help students to master the modern problems of emergency situations. Independent work of students of higher education is a form of organization of the educational process, which ensures their mastery of educational material in the time free from compulsory educational classes. The existence of this form of organization of the educational process in institutions of higher education is provided for by the Law of Ukraine "On Higher Education" (Article 50). The content of the independent work of a student of higher education in the academic discipline "Technogenetic-ecological safety in the conditions of industrial and economic activity" is determined by its program, these methodical instructions for independent work, tasks and instructions of the teacher.
Keywords: methodical instructions; independent work; the event; water objects; environmental safety; industrial and economic activity